DEVELOPING STUDENTS' SPEAKING COMPETENCE THROUGH AUTHENTIC VIDEO MATERIALS IN ENGLISH LANGUAGE TEACHING (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In an increasingly globalised world, the importance of English as a means of communication is undeniable, even for students outside of philological disciplines. This paper investigates the role of authentic video materials in enhancing the speaking competence of non-philological students in English language education. By reviewing theoretical perspectives, presenting empirical findings, and analysing a small-scale experimental study, the paper highlights how real-life audiovisual content improves linguistic proficiency, motivation, and cultural awareness. Practical implications for language instructors and curriculum designers are discussed, with an emphasis on learner-centred and media-integrated teaching methods.